Optimization of Concentric Ring Array Geometry for 3D Beam Scanning - Li Zhang; Yong-Chang Jiao; Bo Chen (International Journal of Antennas and Propagation)
Optimization of the element placement in a concentric ring array for three-dimensional (3D) beam scanning with minimum peak sidelobe levels (SLLs) is addressed in this paper. In order to achieve 3D beam scanning with the lowest peak SLL, both the radius and the element spacing of each ring are optimized. Moreover, the aperture size is a very important constraint for the array, since there is an upper limit for the aperture size of a given array in real-life environment. Hence, in our optimization design, the maximum radius of the concentric ring array is constrained. Through the optimization, the peak SLL of the optimal concentric ring array is about 6 dB lower than that of the uniform concentric ring array, but the directivity is reduced by only 0.3 dB.